Identification of Lanthanide(III) Luminophores in Magnetic Circularly Polarized Luminescence Using Raman Optical Activity Instrumentation - Wu, Tao; Kapitán, Josef; Andrushchenko, Valery; Bouř, Petr (Analytical chemistry, 2017)
Luminescence of lanthanide(III) ions sensitively reflects atomic environment. However, the signal may be weak and covered by Raman scattering. In the present study magnetic circularly polarized luminescence (MCPL) is explored as a more sensitive tool to recognize the lanthanide signal and assign underlying electronic transitions. MCPL spectra of the Na3[Ln(DPA)3] (Ln = Ce, Pr, Nd, Sm, Eu, Tb, Dy, Ho, and Er) complexes were recorded on a Raman optical activity (ROA) instrument. The ROA spectrometer equipped with the 532 nm laser excitation sensitively detects differences in scattering of left- and right-circularly polarized light caused by the magnetic field. Weak bands sometimes invisible in unpolarized measurement could be detected as MCPL. Observed transitions were assigned with the aid of the ligand-field theory. MCPL also reflects the environment: chloride and nitrate salts (LnCl3 and Ln(NO3)3) provide a different signal than the complex; for NdIII the signal responds to distribution of chloride and nitrate ions around the metal. The MCPL technique thus appears useful for identification and assignment of lanthanide transitions and increases the potential of fluorescent probes for applications in analytical chemistry and imaging.